Evaluation of 5-Year Trends in Knee Society Scores Stratified by Comorbidities: A Prospective, Longitudinal Study - Jauregui, Julio J.; Issa, Kimona; Cherian, Jeffrey J.; Harwin, Steven F.; Given, Kristin; Mont, Michael A. (The Journal of Knee Surgery, 2016)
Total knee arthroplasties (TKAs) are reliable procedures for treating end-stage knee osteoarthritis with excellent long-term outcomes. The purpose of this study was to longitudinally evaluate temporal trends of Knee Society Scores (KSS) after TKA and to identify potential demographic and comorbid factors that affect these outcomes. This prospective study evaluated 281 patients (108 men and 173 women) with a mean age of 66 years (range, 39–80 years) who underwent primary TKA (minimum follow-up 5 years). During each follow-up visit, KS objective, function, and total scores were evaluated. The effects of different demographics and comorbidities on outcomes were further analyzed using multivariate regression analysis. Following TKA, peak mean KSS were observed at 1-year follow-up (mean, 92 points), after which there was no significant difference in scores at 5 years compared with 1-year follow-up (mean, 92 points). KS function scores were observed to be unchanged from preoperative levels (mean, 53 points) and at 6 weeks (mean, 56 points). These were significantly higher at 3 months (mean, 78 points) and reached a maximum mean peak at 1 year (mean, 85 points). KS objective scores increased earlier than function scores. The demographic variables and comorbidities that demonstrated a significantly negative impact in KS function scores were increased age, female gender, higher body mass index, and several medical comorbidities including immunological and neurological disease, and neoplasm. Race was the only variable that significantly decreased the KS objective scores. KSS after TKA follow temporal trends with scores initially unchanged from preoperative levels for the objective component, but the scores increased for the functional component. All components demonstrated higher levels compared with preoperative scores by 3 months and peaked at 1-year follow-up. At 5-year follow-up, all mean KSS were unchanged relative to peak scores seen at 1 year. Various patient demographics and comorbidities could potentially have a negative influence on the KSS outcomes. Surgeons should counsel their patients that the full benefit of TKA will be perceived 1 year after surgery, and this level of improvement is likely to remain constant.
Keywords: knee society score; outcomes; total knee arthroplasty; comorbidities; social factors; demographic characteristics